Exact Analytical Solution for Suction and Injection Flow with Thermal Enhancement of Five Nanofluids over an Isothermal Stretching Sheet with Effect of the Slip Model: A Comparative Study - Emad H. Aly; Abdelhalim Ebaid (Abstract and Applied Analysis)
We introduced a direct and effective approach to obtain the exact analytical solution for the nanoparticles-water flow over an isothermal stretching sheet with the effect of the slip model. In particular, we examined and compared the effect of the existence of five metallic and nonmetallic nanoparticles, namely, Silver, Copper, Alumina, Titania, and Silicon Dioxide, in a base of water. The most interesting physical parameters were then discussed in the presence of no-slip model, first order slip, and second order slip parameters. It is found that, with no-slip effect, the present exact solutions are in a very good agreement with the previous published results. On the other hand, with the effect of the slip model, increase in the nanoparticle volume friction decreases the velocity for the high density of nanoparticles, increases it for the low density of them, and increases the temperature for all investigated nanoparticles. Further, increase in the wall mass decreases the velocity and temperature; however, it increases the local skin friction. Furthermore, increase in the slips slows down the velocity, increases the temperature with an impressive effect in the injection case, and decreases the local skin friction and the reduced Nusselt number. It was also demonstrated that, as the nanoparticle becomes heavier, this results in increase and decrease in reduced skin friction coefficient and reduced Nusselt number, respectively, with significant effect in the presence of the second slip. Finally, Silver is the suitable nanoparticle if slowing down the velocity and increasing the temperature are needed; Silicon Dioxide is the appropriate nanoparticle if different behavior is to be considered.